Cyclophosphamide: An Overview - Aditya Kumar Bubna (Clinical Dermatology Review)
Cyclophosphamide (CPE) is an alkylating agent that has shown to have a wide range of applications in dermatology. Although not a first-line drug for any of the dermatological disorders, it has been found to be useful as a second-line drug in unresponsive cases. A major drawback of CPE is its toxicity profile. Nevertheless, if used with caution, it can prove to be of immense value in dermatologic practice.